The Influence of Occupational Safety and Health and the Work Environment on Employee Performance at PT. PLN PDKB KSKT Unit - Edy Mahfuz; Junaidi Junaidi; Muhammad Haris Syafitri; Abdul Kadir; Orbawati Orbawati (International Forum of Researchers and Lecturers, 2025)
Things that is done by the company can be in the form of occupational safety and health training aimed at improving knowledge , skills , attitudes that are physically designed according to the work needs of each employees . In addition , protective equipment is also called Personal Protective Equipment (PPE) which is equipment used by all employees without exception to protect themselves from potential workplace accidents . There are several elements that can support occupational safety , namely elements of occupational safety and security such as awareness in maintaining occupational safety and health , being thorough , implementing work procedures by pay attention to occupational safety and health . Good occupational safety is an important dimensions of employee protection . This protection aiming for employees to safely carry out their daily work so that they can improve industrial productivity performance . PT. PLN (Persero) Unit PDKB KSKT is a State- Owned Enterprise (BUMN) whose purpose is in the field of distributing electrical energy PT. PLN (Persero) serves the electricity needs of the community such as submitting applications for electricity installations , submission applications for increasing voltage or adding power , checking PLN electricity bills , paying electricity to complan